Pencegahan Disabilitas pada Kusta - Thiodorus, Robert; Rusyati, Luh Made Mas; Sadeli, Marrietta Sugiarti (Jurnal Biomedika dan Kesehatan, 2023)
Leprosy, a chronic granulomatous infectious disease caused by Mycobacterium Leprae, presents a complex challenge with profound social, physical, and economic implications. The burden of leprosy is a persistent concern in many developing countries, despite substantial control efforts. The World Health Organization (WHO) initiated the "Global Leprosy Strategy 2016-2020" to combat this issue, focusing on reducing children diagnosed with leprosy, eliminating visible deformities, and enacting anti-discrimination laws. Disability in leprosy is multifaceted and preventing disability in leprosy is a critical endeavor, such as prophylaxis, early diagnosis, and comprehensive care strategies. Vaccination with the BCG vaccine provides moderate protection, and combining it with single-dose rifampicin (SDR) can enhance its effectiveness, particularly for lepromatous cases with delayed diagnoses. Improved training for healthcare providers can facilitate early detection, reducing the risk of disability. After effective leprosy treatment, longterm morbidity remains a concern. Continued education of healthcare workers and communities is pivotal in preventing damage to hands, feet, and eyes, especially in cases of peripheral neuropathy. Disability progression is a substantial risk, highlighting the need for ongoing medical assessments, even post-MDT treatment. Restructuring primary care services to ensure quality post-treatment care is essential. Stigma remains a significant obstacle in leprosy prevention. Community awareness and stigma reduction can motivate individuals to seek treatment. Epidemiological patterns transmission within households, play a crucial role in identifying new cases. Routine examinations of household contacts of leprosy patients can expedite early diagnosis. Nutrition also plays a role in leprosy prevention. Ensuring access to nutritious food is critical to reducing the risk of developing the disease. In conclusion, the prevention of disability in leprosy is a multifaceted endeavor that demands comprehensive strategies, early intervention, awareness, and community engagement. Addressing this issue is vital for improving the quality of life for individuals affected by leprosy and for achieving a leprosy-free world.